Impact of Surrounding Gas Density on the Turbulent Liquid Jet - Said, Muhamad; Abdelsamie, Abouelmagd; Emara, Kareem; Sedrak, Momtaz (Trends in Sciences, 2023)
This numerical study aims to investigate the impact of surrounding gas density on liquid turbulent jet. Incompressible large eddy simulations (LES) with Wall-Adapting Local Eddy-Viscosity (WALE) sub-grid scale model in ANSYS-FLUENT were performed to capture the morphology of the breakup as well as the important flow field characteristics. A volume of fluid (VOF) approach was used to track the unsteady evolution and breakup of the liquid jet. Different variables have been examined to assess this impact. These variables are instantaneous velocity, liquid volume fraction, and turbulent kinetic energy. Also, the centerline values have been investigated to obtain the jet half-width and spray dispersion angle. The jet diameter and exit velocity are 0.2 mm and 100 m/s, respectively. Three different liquid-to-gas density ratios of 54.03, 32.42 and 23.49 are considered, corresponding to ambient gas density of 15, 25 and 34.5 kg/m3, respectively. It has been found that the jet speed and the liquid core length are inversely proportional to the density of the ambient gas. Regarding the liquid core length, it was noted that the effect of gas density on the liquid core length is considerably stronger in the gas density range between 15 - 25 kg/m³ (corresponding to density ratios of 54.03 - 32.42) than that in the range of 25 - 34.5 kg/m³ (corresponding to density ratios of 32.42 - 23.49). The results, also, showed that increasing the gas density leads to an increase in Weber number, which in turn causes a high instability, that makes the breakup initiates closer to the nozzle exit and occurs with higher rate. Likewise, it has been found that the jet width and the spray dispersion angle increase with increasing the gas density. HIGHLIGHTS Spray jets are included in many applications because its important in increasing the heat and mass transfer between the liquid and the surrounding fluid Large eddy simulations (LES) and volume of fluid (VOF) models are used to investigate the characteristics of turbulent liquid jet The investigation was characterized as a function of man variables such as turbulent kinetic energy, liquid potential core, the jet dispersion angle and more The investigation showed that the density of surrounding gas has an influence on the liquid jet characteristics GRAPHICAL ABSTRACT